Feasibility Analysis of Using Electric Vehicle Service in Luang Prabang City - Orphomma, Sounith; Saypaserth, Phetsadachanch; Phoumma, Somphone; Soulisomboon, Dee; Siphaxay, Khamphoungeun; Sengpaseuth, Bouthamaly (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research aims to study the feasibility of using electric vehicles for public transportation services in Luang Prabang city, with objectives to analyze: 1) factors affecting social demand for public electric vehicle services, and 2) economic viability of the investment. The analysis uses SPSS software, with questionnaires designed in Google Forms and actual interviews conducted at the following locations: Souphanouvong University, Night Market, Luang Prabang Provincial Hospital, Airport, Railway Station, and Tad Kuang Si Electric Bus Station. The sampling method was non-probability sampling with a calculated sample size of 400 people, and the collected data was then statistically analyzed. The results of the study were found that: 1). The factors that had the greatest impact on the decision to use electric vehicle services were physical characteristics, personnel, and product aspects. On average, all 7 factors were at a high impact level. It was observed that in the case of studying the satisfaction level of those who had previously used public electric vehicle services, the three factors that users valued most were the same as the factors affecting demand: product aspects, personnel aspects, and physical characteristics. The regarding economic viability, the project evaluation results examined through 4 indicators show: Net Present Value (NPV) of 612,012,960 kip, Investment Return Rate (IRR) of 20.33%, Profitability Index (PI) of 1.14, and Payback Period (PB) of 1 year and 8 months. Based on this analysis, the project is deemed feasible for investment.